2001
DOI: 10.1021/cm011145n
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Properties and Crystal Structure of the Layered Intergrowth Phase Bi3Pb2Nb2O11Cl

Abstract: The crystal structure and physical properties of Bi3Pb2Nb2O11Cl, a member of the Sillen−Aurivillius phase intergrowth family, have been probed using powder neutron diffraction, high-resolution transmission electron microscopy (HRTEM), second harmonic generation (SHG) tests, and alternating current impedance methods. It is shown that this compound undergoes a diffuse ferroelectric type phase transition at T c ∼ 683 K. Although the powder neutron diffraction data show that the crystal structure has pseudo-tetrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…The single-crystal XRD on the platelet crystal revealed that a pseudo-merohedral twin is likely present with domains in the ab plane, in addition to the ferroelectric domains. We also report the growth of single crystal Bi 4 (n = 1, 2, 3, ...) constitutes a promising material platform not only for the photocatalysis but also for ferroelectric [24] or multiferroic properties [25]. We believe that the knowledge of single crystal growth obtained in this study on Bi 4 NbO 8 X can be applied to other Sillén-Aurivillius oxyhalide compounds.…”
Section: Discussionmentioning
confidence: 55%
“…The single-crystal XRD on the platelet crystal revealed that a pseudo-merohedral twin is likely present with domains in the ab plane, in addition to the ferroelectric domains. We also report the growth of single crystal Bi 4 (n = 1, 2, 3, ...) constitutes a promising material platform not only for the photocatalysis but also for ferroelectric [24] or multiferroic properties [25]. We believe that the knowledge of single crystal growth obtained in this study on Bi 4 NbO 8 X can be applied to other Sillén-Aurivillius oxyhalide compounds.…”
Section: Discussionmentioning
confidence: 55%
“…The #uorite-like block consists of fairly regular edge-sharing OBi tetrahedra, which are common to both SilleH n and Aurivillius phases, and also occur, for example, in the MOCuX family of complex oxides, oxyhalides and oxychalcogenides (15). The perovskite-like blocks in the present phases consist of a single octahedral MO layer which is markedly distorted, in contrast to that observed in the n"2 analog, Bi Pb Nb O Cl (9). These distortions are further discussed below.…”
Section: Room-temperature Crystal Structure Of Bi 4 Nbo 8 Br and Bi 4mentioning
confidence: 62%
“…Structurally, Bi NbO Br and Bi TaO Br display very similar distortions to their chloride analogs. It can be seen, for example, that the nature of the distortion of the MO octahedra is the same in each case *M is displaced o!-center towards a face of the octahedron rather than towards an apex, as is found in the A2X1 phase Bi Pb Nb O Cl (9). Also, the distortion around the Bi sites within the [Bi O ] layer is similar*the Bi> lonepair is stereochemically active in elongating the extra-layer Bi}X and Bi}O bonds, while the intra-layer Bi}O bonds remain short.…”
Section: Room-temperature Crystal Structure Of Bi 4 Nbo 8 Br and Bi 4mentioning
confidence: 71%
See 1 more Smart Citation
“…A large number of semiconductor materials as photocatalyst have been developed, such as TiO 2 [2,3], ZnO [4][5][6][7], WO 3 [8,9], BiVO 4 [10][11][12], Bi 2 WO 6 [13,14] and BiOX [15][16][17][18][19][20][21]. However, the low photocatalytic efficiency and unfavorable chemical stability still hinders their practical application in elimination of the environmental hazardous contaminants.…”
Section: Introductionmentioning
confidence: 99%